Analysis of Access to Finance for SMEs in Laos - OUNPHOUVONG, Stamy; KEODUANGKHAM, Phavone; SONESAI, Khamsone (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
SMEs in Lao PDR are growing amid global growth, affecting the adjustment of the domestic economy. Laos has a growing number of small and medium-sized businesses every year, meanwhile, entrepreneurs choose to invest in various sectors, especially SMEs. What businesses in Lao PDR are facing right now is the lack of costs and capital to run their business, and many businesses are using their own capital. Therefore, many businesses seek various sources of funding to support their business, such as loans from banks, financial institutions, and loans from government funds. However, these sources still have limitations that make it difficult for SMEs to access them. This study’s purpose is to investigate the relationship between the decision to apply for bank loans and the characteristics of the business owner/manager and the characteristics of the business. The results show that more experienced, owner-managers running small-size and corporation type businesses in services or manufacturing are more likely to apply for bank loans.